THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES: ITS CONTRIBUTION TO THE DEVELOPMENT OF INTERNATIONAL HUMAN RIGHTS LAW - Paré, Mona (Revista Esmat, 2019)
This article examines the impact that the United Nations Convention on the Rights of Persons with Disabilities (CRPD) has had on international human rights law. While it seems that the convention may have a narrow focus, as it focuses on a specific group of people, this paper argues that it has had an impact on international human rights law more generally. This impact started with the negotiation of the convention between 2002 and 2006, and is continuing with its implementation since its entry into force in 2008. The impact is of both procedural and substantive nature. On the one hand, the procedure that led to the development and adoption of the CRPD was innovative, as are the mechanisms that have been put into place to monitor its implementation. On the other hand, the convention introduces and develops concepts in a novel way in international law, such as new ways of considering the concept of equality, and to understand development, for example. The article concludes that the international community should capitalize on the new approaches, and that their application and interpretation should be closely monitored.